PEMBUATAN KARBON AKTIF DARI CANGKANG BUAH KARET DENGAN AKTIVATOR H3PO¬4 DAN APLIKASINYA SEBAGAI PENJERAP Pb(II) - Joko Murtono; Iriany (Talenta Publisher (Universitas Sumatera Utara), 2017)
Activated carbon necessity in Indonesia was increasing along with the developments of the industriaization era. Based on natural product in Indonesia, probably activated carbon necessity could be guaranteed by domestic production. Rubber shells were solid waste which has potential for multiple uses such as raw materials for the manufacture of activated carbon. In this researched, rubber shells waste were processed into activated charcoal. The aim of this researhed was to determine the effect of the concentration of phosphoric acid activator toward the characteristics of the activated carbon and activated carbon absorption capacity to Pb(II). Shells rubber that passed by the of 100 mesh sieve was impregnated with phosphoric acid (H3PO4) as activator in the ratio fruit shells rubber: phosphoric acid (b:b) of 1:2 and varying concentrations of H3PO4 at 20%, 40%, and 60% for 1 hour. After immersion in the acid, then material was carbonized in a furnace at temperature 500 oC for 1 hour. Surface area of activated carbon was analyzed by usning Braunanear, Emmelt and Teller and concentration of adsorption of Pb(II) was measured by Atomic Absorption Spectroscopy. The results showed the general characteristics of activated carbon comparable to the Indonesian National Standard. The largest adsorption capasity percentage 74% is obtained using Rubber shell activated carbon that activated by 20% phosphoric acid .